In the wake of the great rebellion : Republicanism, agrarianism and banditry in Ireland after 1798 - Patterson, James G. (Book collections on Project MUSE., 2014)
On Monday 19 September 1803, the most significant trial in the history of Ireland took place in Dublin. At the dock stood a twenty-five year old former Trinity College student and doctor's son. His name was Robert Emmet and he was standing trial for heading a rebellion on 23 July 1803. The iconic power of Robert Emmet in Irish history cannot be overstated. Emmet looms large in narratives of the past, yet the rebellion, which he led, remains to be fully contextualised. Patterson's book repairs this omission and explains the complex process of politicisation and revolutionary activity extending.